(untitled) (Journal of Fiber Bioengineering and Informatics, 2013)
The synthesis of nanoparticles from biological processes is evolving a new era of research interests in nanotechnology. Silver nanoparticles are usually synthesized by chemicals which are quite toxic and flammable in nature. This study deals with an environment friendly and biosynthesis process of antibacterial silver nanoparticles using bamboo leaves. The formation and characterisation of AgNPs were confirmed by UV-Vis spectroscopy, energy-dispersive spectroscopy (EDX), X-ray diffraction (XRD) and transmission electron microscope (TEM). The antimicrobial activities were carried out against E. coli and S. aureus strains by using disc diffusion method.